Meta Analysis Study Of Progesterone Receptors Effect on Parturition - R. Zadith Taqwa Swanajadi; Maria Gorreti Marianti Purwanto; Rachmad P Armanto (Healthy-Mu Journal, 2021)
Prematurity is associated with morbidity and mortality. There is alot of causative factors that involved. One of the contributing factors is the presence of uterine contractions that occur prematurely. This is due to a decrease in progesterone levels. This decrease can be achieved by changing the levels of the progesterone receptor (PR) isoform in the myometrium. Objective: To determine whether there is a connection between changes in progesterone receptor isoform levels on labor. This systematic study was arranged according to Prefered Reporting Items For Systematic Review and Meta-Analysis (PRISMA). The articles studied were observational studies. Each article was tested for the quality of the Newcastle-Ottawa Scale literature because the articles used were of the case-control type. From the search results using the search strategy in PUBMED, there were 190 articles that were then selected based on title, abstract, and inclusion and exclusion criteria obtained 4 articles that fit the criteria desired by the researcher. From the results of a systematic study, it was found that the number of progesterone receptor ratios in pregnant women who had spontaneous labor compared to pregnant women who gave birth via planned cesarean section. Pregnancy within labor experienced an increase in the PR-A/PR-B ratio by 1.12 times compared to that of cesarean section delivery.